Implementing Sensory Play with Natural Materials to Improve Fine Motor Development in Early Childhood - Ganti Ritauli Sianturi; Setiyo Utoyo; Delfi Eliza; Yaswinda (Universitas Ahmad Dahlan, 2026)
This study aims to develop a learning model based on sensory play using natural materials to improve fine motor skills in early childhood at Metta Karunia Kindergarten School. The model was developed using a Research and Development (R&D) approach through the ADDIE model stages (Analysis, Design, Development, Implementation, and Evaluation). The model is designed to provide a fun and meaningful learning experience through the exploration of natural materials such as sand, seeds, clay, and gonggong shells. The research results show that the developed learning model is highly valid, with media validation at 81% (fairly valid), material validation at 93% (very valid), and instrument validation at 91% (very valid). The practicality test resulted in a score of 95% (very practical), while the model's effectiveness in improving children's fine motor skills reached 93% (very effective). The final product of this research is a learning model guide that can be used by teachers in thematic learning activities, particularly on the theme of the natural environment. The implications of this study indicate that using sensory play based on natural materials not only supports the development of fine motor skills but also strengthens the values of cooperation and children's creativity. This model is feasible for broader implementation and further development in other learning themes.